2017
DOI: 10.1002/btpr.2487
|View full text |Cite
|
Sign up to set email alerts
|

Alternating flow filtration as an alternative to internal spin filter based perfusion process: Impact on productivity and product quality

Abstract: This article reports the results obtained from comparison of internal spin filter (ISF) and alternating flow filtration (ATF) as cell retention systems, regarding cell growth, volumetric perfusion rate, cell specific perfusion rate and cell productivity in the fermentation process. As expected we were able to reach higher cell densities and to achieve longer runs since ATF systems are known to be less affected by fouling. Volumetric production of the reactor using the ATF system was 50-70% higher than the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…In this study, we didn’t observe membrane plug when we used the standard hollow fiber with pore size 0.2 μm and inner lumen diameter 1 mm, indicating membrane capacity was higher than 100 L / m 2 with the fluxes of 15.4 L/m 2 / day and 30.8 L / m 2 / day. However, we should note that the filtration fluxes used in this study was lower than other reports [20] , [27] , [28] , and the effect of PATFP system on membrane capacity should be further confirmed.…”
Section: Discussioncontrasting
confidence: 41%
“…In this study, we didn’t observe membrane plug when we used the standard hollow fiber with pore size 0.2 μm and inner lumen diameter 1 mm, indicating membrane capacity was higher than 100 L / m 2 with the fluxes of 15.4 L/m 2 / day and 30.8 L / m 2 / day. However, we should note that the filtration fluxes used in this study was lower than other reports [20] , [27] , [28] , and the effect of PATFP system on membrane capacity should be further confirmed.…”
Section: Discussioncontrasting
confidence: 41%
“…A compromise must be found between sufficient time for VI and product loss; therefore, reactors with narrow residence time distribution (RTD) must be used to avoid unnecessary long incubations during continuous operations. While several technologies have been developed for continuous operation in the upstream and downstream processing, virus clearance operations have been neglected. At the same time, continuous VI has also been highlighted as the missing piece of the continuous processing puzzle …”
Section: Introductionmentioning
confidence: 99%
“…Karst et al (2016) evaluated ATF vs. TFF and observed 50% retention in TFF as compared to 10% using ATF in the perfusion bioreactor. In another study, the use of ATF in place of an internal spin filter was studied, and it was found to result in higher cell densities, a higher perfusion rate, higher production (50-70%), and a longer run (Bosco et al, 2017). To overcome the product retention problem associated with TFF-and ATF-based perfusion cultures, a large pore size hollow fiber was recently used and drastically reduced product retention (Wang et al, 2019).…”
Section: Perfusion Culture Processmentioning
confidence: 99%